RESPONSIBLE GAME AND THE RELEASE OF BETS: PSYCHOLOGIST’S PERFORMANCE IN CASE OF INTERVENTION - M. Sant’Anna Bungart, Márcia; Cavalcante Bolor, Simone; Paula Silvestre Basilio da Silva, Ana; Aparecida de Moura Higa, Isabela; Lizak Zolfan, Shirlei (Health and Society, 2024)
With the regulation of online sports bets in Brazil, as established by Law No. 14,790 and its guidelines through Ordinance SPA/MF No. 1,231, there was a large increase in the number of players and frequent adherence to betting platforms. This growth of people adept at betting games brings to light significant concerns related to mental health, because the game disorder, also known as ludopathy, is characterized by excessive and harmful use of this practice. Mental health studies indicate that exacerbated involvement in gambling can lead to the development of serious psychological disorders such as depression, anxiety and stress, especially in cases of frequent financial losses and repeated attempts to recover the damage. This project aims to analyze the contributions of psychology, with emphasis on cognitive behavioral therapy (CBT), in the confrontation and combating symptoms associated with game addiction and online bets. Betting houses, popularly called Bets, have their operation legalized by Law No. 14,790/2023 and, from January 2025, will be authorized to work in Brazil within legal parameters, which will make access wider, requiring measures Preventive and treatment strategies focused on the welfare of players. Research will examine how CBT can contribute to the reduction of negative impacts caused by compulsive use of BETs, identifying risk factors and social and psychological influences that lead to the development of this addiction. CBT -specific techniques will be explored to resignify dysfunctional thoughts, promoting greater emotional and behavioral control of players and contributing to relapse prevention.